Research on Test Method of Foundation Bed Coefficient in Nanjing Soft Soil Area - Min Zhang; Tao Qiu (Geofluids)
Relying on the geotechnical engineering survey project of Nanjing Lukou Airport, this research adopts the method of combining in situ and indoor testing to analyze the coefficient of soil foundation under different conditions (flow plastic, plastic, and soft plastic). Based on the differences in test results, in situ and indoor test methods appropriate for the benchmark bed coefficient of Nanjing soft soil area are proposed. Research findings depicted that the bed coefficients obtained by different methods are not similar; therefore, if the data obtained by different methods need to be compared and analyzed, they have to be unified as K30. Simultaneously, in the indoor test, this study compared the foundation bed coefficient obtained by the consolidation method, the improved K0 instrument consolidation method, and the triaxial method. Results revealed that the improved K0 instrument consolidation method can better realize the test of the soil foundation coefficient. This study can provide a reference for geotechnical investigation and design of soft soil in the study area.